The social construction of young women's identity and sexual decisions - Pule, Neo Tshireletso (University of the Free State, 2009)
The identity, sexual identity and sexual decisions of young women have been explored from a social constructionist perspective in this text. Social constructionism acknowledges multiple realities by recognising that one's understanding of a concept is constructed in terms of where and how one lives. The three concepts are therefore explored in terms of the reality of each of the participants. The writer has focused on the work of Gilligan in describing the possible psychological processes that might be involved in the development of the identity of a young woman. The work of Bowen has also been acknowledged in terms of identity development in family systems. Other research has been explored regarding the social construction of young women's identity, sexual identity and their sexual decisions. Certain research in which information on the experiences of women has been shared in terms of sexuality has also been explored. Previous studies regarding the sexuality and sexual behaviour of young people (male and female) have been consulted in order to gain a better understanding of -the sexual lives of young people. The participants, who were all students at a South African higher education institution were gathered by means of a volunteering system to participate in two focus groups. The focus group discussions included creative or artistic expressions as well as an application of the nominal group technique. The stories of the young women were recorded. The researcher obtained some understanding of these by means of the feminist poststructural discourse analysis. The participants reported that a relationship context is essential for the social construction of the identity of young women. It appeared, from their reports, that connectedness is important in defining identity as a young woman. Furthermore, the participants indicated that a communal artifact, or processes whereby knowledge is interchanged and concepts are negotiated and debated, facilitates the social construction of female sexual identity. They finally reported that one's intrapersonal script appears to inform the sexual decisions of young women. They seemed to hold the view that the intrapersonal script is informed by socialisation, context (family, friends, religion, beliefs etcetera), as well as past experience among other factors. A concept which may be related or identical to the ethic of care as discussed in Gilligan's work seems to play an important role in facilitating and informing the sexual decisions of a young woman.
Dissertation (M.Soc.Sc. (Counselling Psychology))--University of the Free State, 2009
Keywords: Female identity; Sexual identity; Sexual scripts; Female sexuality; Dominant narrative